Pullback Attractors for a Nonautonomous Retarded Degenerate Parabolic Equation - Fahe Miao; Hui Liu; Jie Xin (Discrete Dynamics in Nature and Society)
This paper is devoted to a nonautonomous retarded degenerate parabolic equation. We first show the existence and uniqueness of a weak solution for the equation by using the standard Galerkin method. Then we establish the existence of pullback attractors for the equation by proving the existence of compact pullback absorbing sets and the pullback asymptotic compactness.